2002
DOI: 10.1073/pnas.052124799
|View full text |Cite|
|
Sign up to set email alerts
|

Impaired neural tube closure, axial skeleton malformations, and tracheal ring disruption in TRAF4-deficient mice

Abstract: TRAF4 belongs to the tumor necrosis factor receptor-associated factor (TRAF) family of proteins but, unlike other family members, has not yet been clearly associated to any specific receptor or signaling pathway. To investigate the biological function of TRAF4, we have generated traf4 -deficient mice by gene disruption. The traf4 gene mutation is embryonic lethal but with great individual variation, as approximately one third of the homozygous mutant embryos died… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
129
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(135 citation statements)
references
References 33 publications
(39 reference statements)
3
129
0
3
Order By: Relevance
“…TRAF4 immunohistochemical staining in breast (a, b), ovary (c, d), colon (e, f) and lung (g, h) adenocarcinomas was homogeneous throughout each tumor sample and detects cytoplasmic overexpression in the four different types of cancer (b, d, f and h) ( Â 40 magnification). The anti-TRAF4 monoclonal antibody 5MLN-2H1 was previously described (Regnier et al, 2002). The conditions for detecting TRAF4 above the basal level of expression were assessed using serial antibody dilutions on paraffin sections of HEK 293 cells stably overexpressing TRAF4 versus sections of wild-type cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TRAF4 immunohistochemical staining in breast (a, b), ovary (c, d), colon (e, f) and lung (g, h) adenocarcinomas was homogeneous throughout each tumor sample and detects cytoplasmic overexpression in the four different types of cancer (b, d, f and h) ( Â 40 magnification). The anti-TRAF4 monoclonal antibody 5MLN-2H1 was previously described (Regnier et al, 2002). The conditions for detecting TRAF4 above the basal level of expression were assessed using serial antibody dilutions on paraffin sections of HEK 293 cells stably overexpressing TRAF4 versus sections of wild-type cells.…”
mentioning
confidence: 99%
“…Several reports suggested that TRAF4 could be recruited to different TNFR and TLR signalling pathways (Krajewska et al, 1998;Ye et al, 1999;Esparza and Arch, 2004;Takeshita et al, 2005), and in mitogen-activated protein kinase (MAPK) pathways (Xu et al, 2002;Abell and Johnson, 2005;Li et al, 2005) but in vivo evidence of such a role is still missing. Mice deficient for TRAF4 exhibit clear ontogenic defects affecting neural tube closure, tracheal formation and skeletal patterning, phenotypes that might be linked to abnormal cell migration (Regnier et al, 2002).…”
mentioning
confidence: 99%
“…DTRAF1 seems to control apoptosis and imaginal discs and photosensory neurons development by regulating the activation of JNK and its upstream kinases Hep and DTAK1 62 . The role of TRAF4 in development is also supported by studies in zebra fish (Danio rerio) 63 and mouse 64 , where it has been shown to participate in neurulation in vivo. TRAF4 involvement in JNK activation has been also demonstrated in mammals 65,66 .…”
Section: Evolutionary Aspects Of Trafs Functionmentioning
confidence: 86%
“…Studies using mice deficient in one of the individual Traf gene (Traf1 to Traf6) have helped elucidate the roles of individual TRAF proteins (Xu et al 1996;Yeh et al 1997;Lomaga et al 1999;Naito et al 1999;Nakano et al 1999;Shiels et al 2000;Tsitsikov et al 2001;Regnier et al 2002). Each TRAF molecule differentially regulates intracellular signaling that critically influences the development, homeostasis, and functionality of T cells (Table 1).…”
Section: Roles Of Trafs In T-cell Biologymentioning
confidence: 99%